DEVELOPMENT OF ANSARI LEARNING MODEL BASED ON A PROJECT TO HELP STUDENTS CARRY OUT TEACHING ASSISTANCE AT SCHOOLS - Bansu Irianto Ansari; Suci Maulina; Muhammad Iqbal (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Solving non-routine math word problems is important to do because it will train students’ and teacher students’ creative, critical, collaborative and communicative thinking. Aims of this study are (1) to conduct developmental research to produce a product, that is, an innovative project-based learning model abbreviated as ANSARI (Auditory, Negotiation, Strategies-somatic, Administer Information, Reflection, and Interaction-communication) which is valid, practical and effective, namely the ANSARI model as a learning medium, (2) to find out its effectiveness after being trained on teacher students, teachers and students in schools as a group in solving non-routine word problems. The samples were 145 students from five high schools with different levels in Sigli City, Aceh Province, Indonesia. Data were analyzed quantitatively with One-way Anova and qualitatively to determine students' perceptions. The findings revealed that the ANSARI model has an influence in increasing teacher students’ and school students’ HOTS in the pre-test and post-test as well as students' perceptions of the learning model.